Polyamide resin composition, extrusion-molded article, and method for producing extrusion-molded article

By adding a specific proportion of semi-aromatic polyamide, polyolefin and fatty acid metal salts to the polyamide resin composition, the problems of retention stability, pressure control, surface properties and impact resistance during the extrusion forming process are solved, and the optimization of the performance of the polyamide resin composition in various aspects is achieved.

CN119604581APending Publication Date: 2025-03-11KURARAY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380056656.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-05
Filing Date
2023-07-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

During the extrusion forming process, it is difficult for the polyamide resin composition to achieve retention stability, pressure control, surface properties and impact resistance at the same time, especially in low temperature environments.

Method used

The polyamide resin composition containing semiaromatic polyamides, polyolefins and fatty acid metal salts is prepared and the specific mass ratio, terminal amino concentration and functional group content conditions are met to optimize its forming properties.

Benefits of technology

Excellent retention stability, good pressure control during extrusion forming, high surface properties, softness, chemical reagent resistance and impact resistance in wide temperature areas are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a polyamide resin composition which contains a semi-aromatic polyamide (A), a polyolefin (B), and a fatty acid metal salt (C), satisfies conditions [1]-[5], has excellent retention stability, can suppress pressure increase during extrusion molding, and has excellent heat resistance. The extrusion-molded body has excellent surface properties, flexibility, chemical resistance, and impact resistance in a wide temperature range. [1] The mass MA of the component (A) and the mass MB of the component (B) in the composition are MA / MB = 60 / 40 to 85 / 15; [2] the component (C) in the composition is 0.05-0.5 mass% of the total mass of the components (A) and (B); [3] The terminal amino group concentration [NH2] of component (A) is 45-80 [mu] eq / g, and the terminal carboxyl group concentration [COOH] ([mu] eq / g) of [NH2] and component (A) is 2 < [NH2] / [COOH] < 5. [4] the content ratio of functional groups formed from unsaturated epoxide in component (B) is < = 200 mol / g; [5] The ratio of copper atoms derived from the copper-based stabilizer in the composition is less than or equal to 200 ppm by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyamide resin composition, an extruded molded body thereof, and a method for producing the extruded molded body. Background Art

[0002] Polyamide has excellent strength, heat resistance, chemical resistance, etc., and has been used for automobile fuel pipes, oil or gas transportation pipes, etc.

[0003] The technology of imparting flexibility and impact resistance to polyamide by blending a specific polyolefin having a functional group reactive with polyamide into polyamide has been known for a long time.

[0004] For example, Patent Document 1 discloses a polyamide resin composition comprising a semi-aromatic polyamide and a polyolefin, wherein the semi-aromatic polyamide has terminal groups of a specific semi-aromatic polyamide having a predetermined ratio or more of terminal groups of the molecular chain capped, the amount of residual terminal amino groups being set to a specific range, and the value obtained by dividing the amount of terminal amino groups by the amount of terminal carboxyl groups being set to a predetermined value or more.

[0005] Patent Document 2 discloses a soft polyamide resin composition comprising a specific semi-aromatic polyamide, an olefin-based copolymer, and a stabilizer containing copper, and containing calcium stearate as a processing aid.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-40346

[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-172445 Summary of the invention

[0010] Problems to be solved by the invention

[0011] When a molded article is produced by extrusion molding, the polyamide resin composition is required to have manufacturing stability, retention stability, and low resin pressure during molding in addition to the flexibility, impact resistance, and chemical resistance of the molded article. In addition, in order to withstand use in various environments, it is also required to have impact resistance in a low temperature range.

[0012] Compared with injection molding, extrusion molding has a long residence time in a molten state in a molding machine. Therefore, polyamide resin compositions with an increased amount of elastomer added for the purpose of imparting flexibility, such as the polyamide resin compositions described in Patent Documents 1 and 2, and polyamide resin compositions with an increased concentration of terminal amino groups for the purpose of improving chemical resistance, such as the polyamide resin composition described in Patent Document 1, are likely to result in an increase in melt viscosity during retention and a decrease in retention stability. These problems are more likely to occur in polyamide resin compositions using semi-aromatic polyamides with high melting points.

[0013] Therefore, an object of the present invention is to provide a polyamide resin composition which has excellent retention stability, can suppress pressure increase during extrusion molding, has excellent surface properties of the extruded product, and is also excellent in flexibility, chemical resistance, and impact resistance in a wide temperature range.

[0014] Means for solving problems

[0015] The present inventors have found that the above-mentioned problems can be solved by preparing a polyamide resin composition comprising a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C) and satisfying specific conditions, thereby completing the present invention.

[0016] The present invention relates to the following <1> to <12>.

[0017] <1> A polyamide resin composition comprising a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C), and satisfying the following conditions [1] to [5].

[0018] [1] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=60 / 40 to 85 / 15.

[0019] [2] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.05 to 0.5% by mass based on the total mass of the semi-aromatic polyamide (A) and the polyolefin (B).

[0020] [3] The terminal amino group concentration [NH2] (μeq / g) of the semi-aromatic polyamide (A) is 45 to 80 μeq / g and the ratio of the terminal amino group concentration to the terminal carboxyl group concentration [COOH] (μeq / g) of the semi-aromatic polyamide (A) satisfies the following formula (1).

[0021] 2<[NH2] / [COOH]<5 ···Formula (1)

[0022] [4] The polyolefin (B) does not contain a functional group formed by an unsaturated epoxide, or the content ratio of the functional group formed by an unsaturated epoxide in the polyolefin (B) is 200 μmol / g or less.

[0023] [5] The polyamide resin composition does not contain a copper-based stabilizer, or the copper atomic ratio derived from the copper-based stabilizer in the polyamide resin composition is 200 mass ppm or less.

[0024] <2> The polyamide resin composition according to <1> above, wherein the semi-aromatic polyamide (A) contains 50 mol % or more of at least one selected from terephthalic acid units and naphthalene dicarboxylic acid units based on all dicarboxylic acid units.

[0025] <3> The polyamide resin composition according to <1> or <2>, wherein the semi-aromatic polyamide (A) contains 60 mol % or more of aliphatic diamine units having 7 to 13 carbon atoms or meta-xylylenediamine units based on all diamine units.

[0026] <4> The polyamide resin composition according to <3>, wherein the aliphatic diamine unit having 7 to 13 carbon atoms is a unit derived from at least one aliphatic diamine selected from 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine and 1,10-decanediamine.

[0027] <5> The polyamide resin composition according to <3> or <4>, wherein the aliphatic diamine unit having 7 to 13 carbon atoms is a unit derived from at least one aliphatic diamine selected from 1,9-nonanediamine and 2-methyl-1,8-octanediamine.

[0028] <6> The polyamide resin composition according to any one of <1> to <5>, wherein the polyolefin (B) is a modified polyolefin modified with at least one selected from the group consisting of α,β-unsaturated carboxylic acids and derivatives thereof.

[0029] <7> The polyamide resin composition according to any one of <1> to <6>, wherein the fatty acid metal salt (C) is a metal salt of a fatty acid having 10 to 28 carbon atoms.

[0030] <8> The polyamide resin composition according to any one of <1> to <7>, wherein the fatty acid metal salt (C) is selected from calcium stearate, magnesium stearate and zinc stearate.

[0031] <9> The polyamide resin composition according to any one of <1> to <8>, further comprising an antioxidant.

[0032] <10> An extrusion molded product, which is an extrusion molded product of the polyamide resin composition according to any one of <1> to <9>.

[0033] <11> The extruded article according to <10>, which is a chemical pipe, a composite pipe, a rodless production pipe, an onshore oil pipeline, an offshore oil pipeline, a geothermal flow pipe, an umbilical pipe, or a flexible pipe.

[0034] <12> A method for producing an extrusion molded article, comprising heating and melting the polyamide resin composition according to any one of <1> to <9>, and extruding the molten polyamide resin composition to obtain an extrusion molded article.

[0035] Effects of the Invention

[0036] According to the present invention, a polyamide resin composition can be provided which has excellent retention stability, can suppress pressure increase during extrusion molding, has excellent surface properties of the extruded product, and is also excellent in flexibility, chemical resistance, and impact resistance in a wide temperature range. DETAILED DESCRIPTION

[0037] Hereinafter, embodiments of the present invention will be described.

[0038] Any form of selecting or combining the matters described in this specification at random is also included in the present invention.

[0039] In the present specification, preferred provisions can be arbitrarily selected, and a combination of preferred provisions can be said to be more preferred.

[0040] In this specification, the description "XX to YY" means "XX or more and YY or less".

[0041] In this specification, for a preferred numerical range (e.g., a range of content, etc.), the lower limit and upper limit values ​​described in stages can be independently combined. For example, according to a description such as "preferably 10 to 90, more preferably 30 to 60", the "preferable lower limit (10)" and the "more preferably upper limit (60)" can be combined to set to "10 to 60".

[0042] [Polyamide resin composition]

[0043] The polyamide resin composition according to an embodiment of the present invention comprises a semi-aromatic polyamide (A), a polyolefin (B), and a fatty acid metal salt (C), and satisfies the following conditions [1] to [5].

[0044] [1] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=60 / 40 to 85 / 15.

[0045] [2] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.05 to 0.5% by mass based on the total mass of the semi-aromatic polyamide (A) and the polyolefin (B).

[0046] [3] The terminal amino group concentration [NH2] (μeq / g) of the semi-aromatic polyamide (A) is 45 to 80 μeq / g and the ratio of the terminal amino group concentration to the terminal carboxyl group concentration [COOH] (μeq / g) of the semi-aromatic polyamide (A) satisfies the following formula (1).

[0047] 2<[NH2] / [COOH]<5 ···Formula (1)

[0048] [4] The polyolefin (B) does not contain a functional group formed by an unsaturated epoxide, or the content ratio of the functional group formed by an unsaturated epoxide in the polyolefin (B) is 200 mol / g or less.

[0049] [5] The polyamide resin composition does not contain a copper-based stabilizer, or the copper atomic ratio derived from the copper-based stabilizer in the polyamide resin composition is 200 mass ppm or less.

[0050] As specified in the above condition [1], by setting the ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition to MA / MB = 60 / 40 to 85 / 15, the polyolefin (B) exists in the form of a phase dispersed in the matrix of the semi-aromatic polyamide (A), thereby achieving good flexibility.

[0051] In addition, as specified in the above condition [2], by setting the content of the fatty acid metal salt (C) in the polyamide resin composition to 0.05 to 0.5% by mass relative to the total mass of the semi-aromatic polyamide (A) and the polyolefin (B), it is easy to obtain an extruded product with excellent production stability, excellent extrusion moldability, and excellent surface properties.

[0052] In addition, as specified in the above condition [3], by setting the terminal amino group concentration [NH2] (μeq / g) of the semi-aromatic polyamide (A) to 45 to 80 μeq / g and the ratio of the terminal amino group concentration to the terminal carboxyl group concentration [COOH] (μeq / g) of the semi-aromatic polyamide (A) to satisfy the above formula (1), good chemical resistance and retention stability can be ensured.

[0053] In addition, as specified in the above condition [4], by making the polyolefin (B) contain no functional group formed by an unsaturated epoxide, or by making the content ratio of the functional group formed by an unsaturated epoxide in the polyolefin (B) be 200 mol / g or less, the effect of the fatty acid metal salt (C) can be maximized and good molding processability can be obtained.

[0054] In addition, as specified in the above condition [5], by making the above polyamide resin composition free of a copper-based stabilizer, or by making the content of the copper-based stabilizer in the above polyamide resin composition be 200 mass ppm or less, a polyamide resin composition having excellent retention stability during melting and excellent surface properties of the obtained extruded molded product can be produced.

[0055] When a molded article is to be produced by extrusion molding, the polyamide resin composition is required to have production stability, retention stability, and low resin pressure during molding in addition to flexibility, impact resistance, and chemical resistance of the molded article.

[0056] As described above, Patent Document 1 proposes a polyamide resin composition in which a modified polyolefin is blended into a specific semi-aromatic polyamide, and the [NH2] / [COOH] value of the semi-aromatic polyamide is focused to achieve [NH2] / [COOH]≥6.

[0057] However, if the amount of [NH2] present is too large, it is not conducive to long-term retention stability and it is difficult to improve the ease of production of extrusion molding. Therefore, it is considered to make the value of [NH2] / [COOH] of the semi-aromatic polyamide less than 6.

[0058] However, the present inventors' research has revealed that when [NH2] is reduced in order to reduce the value of [NH2] / [COOH] and thereby achieve long-term retention stability, any of the above-mentioned other characteristics (i.e., manufacturing stability, low resin pressure during molding, and softness, impact resistance, and chemical resistance of the molded body) is likely to be reduced. Furthermore, the present inventors have found that when [NH2] is reduced, long-term retention stability and the above-mentioned characteristics can be fully ensured by satisfying the prescribed conditions, thereby completing the present invention.

[0059] In more detail, the present inventors have discovered that, when [NH2] is small, by containing a large amount of polyolefin and a predetermined amount of fatty acid metal salt to reduce the resin pressure, the increase in resin pressure during extrusion molding can be suppressed. Furthermore, in this case, by sufficiently reducing the content of the copper-based stabilizer, it is effective to ensure the above-mentioned characteristics, thereby completing the present invention.

[0060] The reason why the increase in resin pressure during extrusion molding is suppressed by using a specified amount of fatty acid metal salt is not limited to this. It is considered that the fatty acid metal salt enters the semi-aromatic polyamide as the main component, thereby easing the close contact of the polyamide chain, and the sliding property between the polyamide resin composition and the molding machine is improved, resulting in the suppression of the increase in resin pressure during extrusion molding.

[0061] By making the polyamide resin composition fully satisfy the above conditions [1] to [5], it is possible to produce a polyamide resin composition that has excellent retention stability, can suppress pressure increase during molding, has excellent surface properties of its extruded molded product, and also has excellent flexibility, chemical resistance, and impact resistance in a wide temperature range.

[0062] Hereinafter, each component constituting the polyamide resin composition will be described.

[0063] <Semi-aromatic polyamide (A)>

[0064] The polyamide resin composition contains at least one semi-aromatic polyamide (A).

[0065] The semi-aromatic polyamide (A) contains at least one repeating unit formed by polycondensation of a dicarboxylic acid unit and a diamine unit.

[0066] Examples of the dicarboxylic acid unit include aromatic dicarboxylic acid units such as terephthalic acid unit, naphthalene dicarboxylic acid unit, isophthalic acid unit, 1,4-phenylenedioxydiacetic acid unit, 1,3-phenylenedioxydiacetic acid unit, biphenylcarboxylic acid unit, diphenylmethane-4,4'-dicarboxylic acid unit, diphenylsulfone-4,4'-dicarboxylic acid unit, and 4,4'-biphenylcarboxylic acid unit.

[0067] Examples of the naphthalene dicarboxylic acid unit include units derived from 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, and 1,4-naphthalene dicarboxylic acid, and a 2,6-naphthalene dicarboxylic acid unit is preferred.

[0068] In addition, examples of the dicarboxylic acid unit include units derived from aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, dimethylmalonic acid, 2,2-diethylsuccinic acid, 2,2-dimethylglutaric acid, 2-methyladipic acid, trimethyladipic acid, and dimer acid; and units derived from alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, cycloheptanedicarboxylic acid, cyclooctanedicarboxylic acid, and cyclodecanedicarboxylic acid.

[0069] The units derived from dicarboxylic acids may contain only one type or two or more types in the above-mentioned dicarboxylic acid units.

[0070] The semi-aromatic polyamide (A) preferably contains 50 mol% or more of at least one selected from terephthalic acid units and naphthalene dicarboxylic acid units relative to all dicarboxylic acid units. In addition, from the viewpoint of easily obtaining good chemical resistance and heat resistance, the semi-aromatic polyamide (A) more preferably contains 75 mol% or more of at least one selected from terephthalic acid units and naphthalene dicarboxylic acid units relative to all dicarboxylic acid units, and further preferably contains 90 mol% or more.

[0071] Examples of the diamine unit include those derived from linear aliphatic diamines such as 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, and 1,13-tridecanediamine; and those derived from 2-methyl-1,3-propylenediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6 The unit may contain one or more of branched aliphatic diamines such as hexanediamine, 2-methyl-1,8-octanediamine, 2-ethyl-1,7-heptanediamine, and 5-methyl-1,9-nonanediamine; alicyclic diamines such as cyclohexanediamine, methylcyclohexanediamine, and isophoronediamine; aromatic diamines such as p-phenylenediamine, m-phenylenediamine, xylylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, and 4,4'-diaminodiphenyl ether.

[0072] The semi-aromatic polyamide (A) preferably contains 60 mol% or more of an aliphatic diamine unit having 7 to 13 carbon atoms or a meta-xylylenediamine unit relative to all diamine units. If a semi-aromatic polyamide (A) containing an aliphatic diamine unit having 7 to 13 carbon atoms in the above ratio is used, a polyamide resin composition having excellent toughness, heat resistance, chemical resistance, and lightness can be obtained. The semi-aromatic polyamide (A) more preferably contains 75 mol% or more of at least one selected from aliphatic diamine units having 7 to 13 carbon atoms relative to all diamine units, and further preferably contains 90 mol% or more.

[0073] From the viewpoint of obtaining a polyamide resin composition having further excellent heat resistance, low water absorption and chemical liquid resistance, the aliphatic diamine unit having 7 to 13 carbon atoms is preferably a unit derived from at least one aliphatic diamine selected from 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine and 1,10-decanediamine, and more preferably a unit derived from at least one aliphatic diamine selected from 1,9-nonanediamine and 2-methyl-1,8-octanediamine.

[0074] When the aliphatic diamine unit contains units derived from both 1,9-nonanediamine and 2-methyl-1,8-octanediamine, the molar ratio of the 1,9-nonanediamine unit to the 2-methyl-1,8-octanediamine unit is preferably in the range of 1,9-nonanediamine unit / 2-methyl-1,8-octanediamine unit=95 / 5 to 40 / 60, more preferably in the range of 90 / 10 to 40 / 60, and further preferably in the range of 80 / 20 to 40 / 60.

[0075] The semi-aromatic polyamide (A) preferably comprises a dicarboxylic acid unit mainly composed of an aromatic dicarboxylic acid unit and a diamine unit mainly composed of an aliphatic diamine unit having 7 to 13 carbon atoms. Here, "main component" means constituting 50 to 100 mol %, preferably 60 to 100 mol % of all units.

[0076] Examples of the semi-aromatic polyamide (A) include polynonane terephthalamide (polyamide 9T), poly(2-methyloctamethylene) terephthalamide (nylon M8T), polynonane terephthalamide / poly(2-methyloctamethylene) terephthalamide copolymer (nylon 9T / M8T), polynonane naphthalamide (polyamide 9N), polynonane naphthalamide / poly(2-methyloctamethylene) naphthalamide copolymer (nylon 9N / M8N), polydecane terephthalamide (polyamide 10T), and a copolymer of polyamide 10T and polyundecanamide (polyamide 11) (polyamide 10T / 11).

[0077] Among them, at least one selected from polyamide 10T / 11, polynonane naphthalamide (polyamide 9N), polynonane naphthalamide / poly (2-methyloctamethylene) naphthalamide copolymer (nylon 9N / M8N), polynonane terephthalamide (polyamide 9T), polynonane terephthalamide / poly (2-methyloctamethylene) terephthalamide copolymer (nylon 9T / M8T) and polydecane terephthalamide (polyamide 10T) is preferred, and polynaphthalamide is more preferred. At least one of a polynonanediamine / poly(2-methyloctamethylene)naphthalamide copolymer (nylon 9N / M8N), a polynonaneterephthalamide / poly(2-methyloctamethylene)terephthalamide copolymer (nylon 9T / M8T), and polyamide 10T / 11 is preferred. From the viewpoint of ensuring moldability and rigidity at high temperatures, a polynonaneterephthalamide / poly(2-methyloctamethylene)terephthalamide copolymer (nylon 9T / M8T) is further preferred.

[0078] In addition, as the semi-aromatic polyamide (A), a semi-aromatic polyamide containing a dicarboxylic acid unit having an aliphatic dicarboxylic acid unit as a main component and a diamine unit having an aromatic diamine unit as a main component can also be used. As the aliphatic dicarboxylic acid unit, there can be mentioned a unit derived from the above-mentioned aliphatic dicarboxylic acid, and one or more of them can be contained. In addition, as the aromatic diamine unit, there can be mentioned a unit derived from the above-mentioned aromatic diamine, and one or more of them can be contained. In addition, other units can be contained within a range that does not hinder the effect of the present invention.

[0079] Examples of the semi-aromatic polyamide including a dicarboxylic acid unit mainly composed of an aliphatic dicarboxylic acid unit and a diamine unit mainly composed of an aromatic diamine unit include poly(meta-xylylene adipamide) (MXD6) and poly(p-xylylene sebacoamide) (PXD10).

[0080] The semi-aromatic polyamide (A) preferably has 10 mol % or more of the terminal groups of the molecular chain capped with a capping agent. When a semi-aromatic polyamide (A) having a capping ratio of 10 mol % or more is used, a polyamide resin composition having better physical properties such as melt stability and hot water resistance can be obtained.

[0081] As the end-capping agent, a monofunctional compound reactive with the terminal amino group or the terminal carboxyl group can be used. Specifically, monocarboxylic acids, acid anhydrides, monoisocyanates, monoacyl halides, monoesters, monoalcohols, monoamines, etc. can be cited. From the viewpoints of reactivity and stability of the end-capping terminal, monocarboxylic acids are preferred as the end-capping agent for the terminal amino group, and monoamines are preferred as the end-capping agent for the terminal carboxyl group. From the viewpoints of ease of operation, monocarboxylic acids are more preferred as the end-capping agent.

[0082] As the monocarboxylic acid used as the end-capping agent, there is no particular limitation as long as it is reactive with the amino group. As the monocarboxylic acid, for example, there can be mentioned aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, isobutyric acid, etc.; alicyclic monocarboxylic acids such as cyclopentanecarboxylic acid and cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthoic acid, β-naphthoic acid, methylnaphthoic acid, phenylacetic acid, etc.; any mixture thereof, etc. Among them, from the aspects of reactivity, stability of the end-capping end, price, etc., it is preferred to be selected from at least one of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid and benzoic acid.

[0083] The monoamine used as the end-capping agent is not particularly limited as long as it is reactive with the carboxyl group. Examples of the monoamine include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine; and any mixture thereof. Among them, from the perspectives of reactivity, high boiling point, stability of the end-capping terminal, and price, it is preferred to select at least one of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline.

[0084] The intrinsic viscosity η of the semi-aromatic polyamide (A) is measured at a concentration of 0.2 g / dl and a temperature of 30°C using concentrated sulfuric acid as a solvent. inh It is preferably 0.6 dl / g or more, more preferably 0.8 dl / g or more, further preferably 0.9 dl / g or more, and particularly preferably 1.0 dl / g or more. In addition, the above-mentioned intrinsic viscosity is preferably 2.0 dl / g or less, more preferably 1.8 dl / g or less, and further preferably 1.6 dl / g or less. If the intrinsic viscosity η of the semi-aromatic polyamide (A) is inh When the content is within the above range, various physical properties such as moldability are further improved.

[0085] Intrinsic viscosity η inh It can be determined by the following formula (P) from the flow time t0 (seconds) of the solvent (concentrated sulfuric acid), the flow time t1 (seconds) of the sample solution, and the sample concentration c (g / dl) in the sample solution (ie, 0.2 g / dl).

[0086] η inh = [ln (t1 / t0)] / c Formula (P)

[0087] As specified in the above condition [3], the content of terminal amino groups (hereinafter also referred to as "terminal amino group content") ([NH2]) of the semi-aromatic polyamide (A) is 45 to 80 μeq / g, preferably 45 to 75 μeq / g, more preferably 45 to 70 μeq / g, and even more preferably 45 to 65 μeq / g.

[0088] If the terminal amino group content ([NH2]) is 45 μeq / g or more, the polyamide resin composition has good chemical resistance. If the terminal amino group content is 80 μeq / g or less, when a modified polyolefin described later is used as the polyolefin (B), gelation due to excessive reaction between the terminal amino group and the modified portion of the polyolefin (B) can be avoided.

[0089] The terminal amino group content ([NH2]) referred to in this specification refers to the amount of terminal amino groups contained in 1 g of the semi-aromatic polyamide (A) (unit: μeq), which can be determined by a neutralization titration method using an indicator. Specifically, [NH2] is measured by the procedure described in the Examples.

[0090] As specified in the above condition [3], the ratio [NH2] / [COOH] of the terminal amino group content [NH2] and the terminal carboxyl group [COOH] of the semi-aromatic polyamide (A) is greater than 2 and less than 5. If [NH2] / [COOH] is greater than 2, chemical resistance can be sufficiently ensured, and if [NH2] / [COOH] is less than 5, retention stability can be sufficiently ensured.

[0091] The terminal carboxyl group content ([COOH], unit: μeq / g) of the semi-aromatic polyamide can be measured by potentiometric titration using a reagent, and specifically, can be measured according to the procedure described in Examples.

[0092] The semi-aromatic polyamide (A) comprising a dicarboxylic acid unit and a diamine unit and having a terminal amino group content ([NH 2 ]) and a terminal carboxyl group content ([COOH]) within the above ranges can be produced, for example, as follows.

[0093] First, dicarboxylic acid, diamine, and, if necessary, aminocarboxylic acid, lactam, catalyst, and end-capping agent are mixed to produce nylon salt. At this time, if the number of moles of all carboxyl groups (X) and the number of moles of all amino groups (Y) contained in the above-mentioned reaction raw materials satisfy the following formula (Q) for calculating the excess,

[0094] -0.5≤[(YX) / Y]×100≤2.0 Formula (Q)

[0095] This is preferred because it is easy to produce a semi-aromatic polyamide (A) having a terminal amino group content ([NH2]) and a terminal carboxyl group content ([COOH]) of 10 to 70 μeq / g.

[0096] Next, the generated nylon salt is heated to a temperature of 200 to 250°C to obtain an intrinsic viscosity η at 30°C in concentrated sulfuric acid. inh The prepolymer having an intrinsic viscosity η of 0.10 to 0.60 dlL / g can be further polymerized to obtain a semi-aromatic polyamide (A). inh When the content is within the range of 0.10 to 0.60 dLl / g, the deviation of the molar balance between carboxyl groups and amino groups and the decrease in polymerization rate in the stage of high polymerization degree are small, the molecular weight distribution is small, and the semi-aromatic polyamide (A) having excellent various properties and moldability can be obtained.

[0097] In the case of the stage of high polymerization degree by solid phase polymerization, it is preferably carried out under reduced pressure or inert gas flow. If the polymerization temperature is in the range of 200 to 280° C., the polymerization rate is high, the productivity is excellent, and coloring and gelation can be effectively suppressed. In addition, in the case of the stage of high polymerization degree by melt extruder, the polymerization temperature is preferably 370° C. or lower. If the polymerization is carried out under the above conditions, the semi-aromatic polyamide (A) is hardly decomposed, and a semi-aromatic polyamide (A) with little deterioration can be obtained.

[0098] The melting point of the semi-aromatic polyamide (A) is not particularly limited, and from the viewpoint of ensuring good heat resistance, it can be, for example, 240° C. or higher, 250° C. or higher, or 260° C. or higher. The upper limit of the melting point of the semi-aromatic polyamide (A) is not particularly limited, but in consideration of moldability, it is preferably 310° C. or lower, more preferably 300° C. or lower, and even more preferably 280° C. or lower.

[0099] The melting point of the semi-aromatic polyamide (A) can be measured in accordance with ISO 11357-3 (2011 2nd edition), and specifically, can be measured according to the procedure described in Examples.

[0100] (Content ratio of semi-aromatic polyamide (A))

[0101] The content of the semi-aromatic polyamide (A) contained in the polyamide resin composition of the present embodiment is preferably 60 to 85% by mass, and more preferably 70 to 85% by mass, relative to 100% by mass of the polyamide resin composition. When the content of the semi-aromatic polyamide (A) is within the above range, a composition having further excellent chemical resistance and heat resistance, and excellent processing stability during melt kneading, flexibility, and impact resistance can be obtained.

[0102] Examples of the catalyst that can be used when producing the semi-aromatic polyamide (A) include phosphoric acid, phosphorous acid, hypophosphorous acid, or salts or esters thereof. Examples of the salts or esters include salts of phosphoric acid, phosphorous acid, or hypophosphorous acid with a metal such as potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, antimony, etc.; ammonium salts of phosphoric acid, phosphorous acid, or hypophosphorous acid; and ethyl, isopropyl, butyl, hexyl, isodecyl, octadecyl, decyl, stearyl, phenyl, etc., of phosphoric acid, phosphorous acid, or hypophosphorous acid.

[0103] The usage amount of the above-mentioned catalyst is preferably more than 0.01 mass % relative to the gross mass 100 mass % of raw material, more preferably more than 0.05 mass %, in addition, preferably below 1.0 mass %, more preferably below 0.5 mass %. If the usage amount of the catalyst is more than the above-mentioned lower limit, then it is easy to polymerize well. If it is below the above-mentioned upper limit, then it is difficult to produce impurities from the catalyst, for example, when the polyamide resin composition is extruded, it is easy to prevent the undesirable conditions caused by the above-mentioned impurities.

[0104] <Polyolefin (B)>

[0105] The polyamide resin composition of the present embodiment comprises a semi-aromatic polyamide (A) and a polyolefin (B), wherein the polyolefin (B) is present as a phase dispersed in a matrix of the semi-aromatic polyamide (A). The polyolefin (B) is preferably a modified polyolefin modified with at least one selected from α,β-unsaturated carboxylic acids and derivatives thereof.

[0106] Examples of the (unmodified) resin serving as the base of the polyolefin (B) include low-density polyethylene, medium-density polyethylene, high-density polyethylene, polypropylene, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-propylene-diene copolymers, ethylene-vinyl acetate copolymers, ethylene-vinyl acetate copolymer saponification products, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, ethylene-acrylic acid methyl copolymers, ethylene-methyl methacrylate copolymers, ethylene-ethyl acrylate copolymers, and polybutadiene.

[0107] Examples of α,β-unsaturated carboxylic acids and derivatives thereof include α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid. In addition, examples of unsaturated compounds having an acid anhydride group include dicarboxylic anhydrides having an α,β-unsaturated bond such as maleic anhydride and itaconic anhydride. As unsaturated compounds having a carboxyl group and / or an acid anhydride group, dicarboxylic anhydrides having an α,β-unsaturated bond are preferred, and maleic anhydride is more preferred.

[0108] The content of the carboxyl group and the acid anhydride group in the polyolefin (B) is preferably in the range of 25 to 200 μmol / g, more preferably in the range of 50 to 100 μmol / g. When the content of the functional group is 25 μmol / g or more, the effect of improving the impact resistance is sufficient. On the other hand, when the content of the functional group is 200 μmol / g or less, the fluidity of the obtained polyamide resin composition is not easily reduced, and the reduction in moldability is suppressed.

[0109] The polyolefin (B) contained in the polyamide resin composition of the present embodiment does not contain a functional group formed by an unsaturated epoxide, or the content ratio of the functional group formed by an unsaturated epoxide in the polyolefin (B) is 200 μmol / g or less, as specified in the above condition [4]. By making the polyolefin (B) contain no functional group formed by an unsaturated epoxide, or making the content ratio of the functional group formed by an unsaturated epoxide in the polyolefin (B) within the above range, the effect of the fatty acid metal salt (C) can be maximized, and good molding processability can be obtained.

[0110] From the viewpoint of further improving the molding processability, the content ratio is preferably 100 μmol / g or less, more preferably 50 μmol / g or less, further preferably 20 μmol / g or less, and particularly preferably 0 μmol / g (i.e., the polyolefin (B) does not contain a functional group consisting of an unsaturated epoxide).

[0111] In addition, in this specification, the content ratio EPO of the functional group formed by the unsaturated epoxide in the polyolefin (B) is calculated according to the following formula (R).

[0112] EPO=100×N×W / M formula (R)

[0113] In the above formula (R), M, W and N are respectively as follows.

[0114] M: molecular weight of the unsaturated epoxide

[0115] W: mass ratio (mass %) of the unsaturated epoxide contained in the polyolefin (B).

[0116] N: mass ratio of the polyolefin (B) per unit mass of the polyamide resin composition (mass %)

[0117] It should be noted that the above-mentioned W can be measured by a common method in the technical field such as a nuclear magnetic resonance apparatus (NMR).

[0118] Examples of the functional group formed from an unsaturated epoxide include aliphatic glycidyl ethers and esters such as allyl glycidyl ether, vinyl glycidyl ether, glycidyl maleate, glycidyl itaconate, glycidyl acrylate, and glycidyl methacrylate; and alicyclic glycidyl ethers and esters such as 2-cyclohexen-1-yl glycidyl ether, cyclohexene-4,5-dicarboxylic acid diglycidyl ester, cyclohexene-4-carboxylic acid glycidyl ester, 5-norbornene-2-methyl-2-carboxylic acid glycidyl ester, and endo-cis-bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic acid diglycidyl ester.

[0119] (Content ratio of polyolefin (B))

[0120] The content of the polyolefin (B) contained in the polyamide resin composition of the present embodiment is preferably 15 to 40% by mass, more preferably 15 to 30% by mass, relative to 100% by mass of the polyamide resin composition. When the content of the polyolefin (B) is within the above range, a polyamide resin composition having excellent processing stability, flexibility, and impact resistance during melt kneading can be easily obtained.

[0121] (Ratio of semi-aromatic polyamide (A) to polyolefin (B))

[0122] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition of the present embodiment is MA / MB=60 / 40 to 85 / 15 as specified in the above condition [1]. When MA / MB is within this numerical range, the polyolefin (B) exists in the form of a phase dispersed in the matrix of the semi-aromatic polyamide (A), and good flexibility can be exhibited.

[0123] From the viewpoint of making it easier to disperse the polyolefin (B), MA / MB is preferably 63 / 37 to 84 / 16, more preferably 68 / 32 to 83 / 17, and even more preferably 68 / 32 to 82 / 18.

[0124] From the viewpoint of further improving extrusion moldability, MA / MB may be set to, for example, 73 / 27 to 85 / 15, 75 / 25 to 85 / 15, or 77 / 23 to 85 / 15.

[0125] From the viewpoint of easily improving the elongation characteristics of a molded body obtained by extrusion molding, MA / MB may be set to, for example, 60 / 40 to 78 / 22, 60 / 40 to 76 / 14, or 60 / 40 to 75 / 25.

[0126] <Metal salt of fatty acid (C)>

[0127] The polyamide resin composition of the present embodiment contains a fatty acid metal salt (C). By containing the fatty acid metal salt (C), it is possible to suppress the pressure increase during molding and obtain an extruded molded product having excellent surface properties.

[0128] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.05 to 0.5% by mass relative to the total mass of the semi-aromatic polyamide (A) and the polyolefin (B), as specified in the above condition [2]. When the content of the fatty acid metal salt (C) is within the above range, an extruded article having excellent manufacturing stability, excellent extrusion moldability, and excellent surface properties can be easily obtained.

[0129] The content of the fatty acid metal salt (C) in the polyamide resin composition is preferably 0.07 to 0.5% by mass, more preferably 0.08 to 0.5% by mass, from the viewpoint of easily improving processability and extrusion moldability.

[0130] From the viewpoint of suppressing an increase in resin pressure during extrusion molding and easily ensuring the elongation characteristics of the obtained molded body, the content of the fatty acid metal salt (C) in the polyamide resin composition may be, for example, 0.2 to 0.5 mass %, 0.2 to 0.4 mass %.

[0131] Preferred fatty acid metal salts (C) include metal salts of fatty acids having 10 to 28 carbon atoms. Examples thereof include zinc stearate, zinc laurate, zinc octoate, zinc behenate, zinc montanate, zinc melissate, calcium laurate, barium laurate, lithium laurate, cobalt stearate, potassium stearate, lithium stearate, barium stearate, calcium stearate, magnesium stearate, aluminum stearate, sodium stearate, nickel stearate, lead stearate, copper (II) stearate, calcium behenate, zinc behenate, magnesium behenate, lithium behenate, sodium behenate, silver behenate, calcium montanate, magnesium montanate, aluminum montanate, lithium montanate, and sodium montanate. In particular, at least one selected from calcium stearate, magnesium stearate, and zinc stearate is more preferred.

[0132] <Copper stabilizer>

[0133] In order to achieve excellent retention stability during melting and surface properties of the obtained extruded molded product, the polyamide resin composition of the present embodiment does not contain a copper stabilizer, or the content of the copper stabilizer is sufficiently small. Specifically, as specified in the above condition [5], the polyamide resin composition does not contain a copper stabilizer, or the copper atomic ratio derived from the copper stabilizer in the polyamide resin composition is 200 mass ppm or less.

[0134] From the viewpoint of improving the retention stability and the surface properties of the extruded product, the ratio of copper atoms derived from the copper-based stabilizer in the polyamide resin composition is preferably 100 mass ppm or less, more preferably 50 mass ppm or less, further preferably 20 mass ppm or less, and particularly preferably 0 mass ppm (i.e., no copper atoms derived from the copper-based stabilizer are contained).

[0135] The copper atomic ratio can be quantified by X-ray photoelectron spectroscopy (XPS) etc. For example, by determining the ratio of the halogen content to the copper atom content, which can be measured by XPS etc. in the same way as copper atoms, it can be identified that the copper component is derived from the copper-based stabilizer.

[0136] The copper atomic ratio can be determined by, for example, using an X-ray photoelectron spectroscopy analyzer (PHI Quantera SXM, manufactured by ULVAC-PHI Co., Ltd.) with Al as the counter cathode to measure the copper atomic ratio in the polyamide resin composition.

[0137] The copper-based stabilizer is a mixture of a copper compound and a metal halide.

[0138] Examples of the copper compound contained in the copper-based stabilizer include copper halides, copper acetate, copper propionate, copper benzoate, copper adipate, copper terephthalate, copper isophthalate, copper salicylate, copper nicotinate, copper stearate, and copper complexes coordinated with chelating agents such as ethylenediamine and ethylenediaminetetraacetic acid.

[0139] Examples of the copper halide include copper iodide; copper bromides such as cuprous bromide and cupric bromide; and copper chlorides such as cuprous chloride.

[0140] The metal halide contained in the copper-based stabilizer is a metal halide that does not correspond to a copper compound, and examples thereof include potassium iodide, potassium bromide, potassium chloride, sodium iodide, sodium chloride, and the like.

[0141] As the copper-based stabilizer, among copper compounds and metal halides, a mixture of at least one copper compound selected from copper iodide, copper bromide and copper acetate and at least one metal halide selected from potassium iodide and potassium bromide is often used.

[0142] <Other additives>

[0143] The polyamide resin composition of the present embodiment may contain other additives other than the copper-based stabilizer as necessary, in addition to the semi-aromatic polyamide (A), the polyolefin (B), and the fatty acid metal salt (C).

[0144] As the above-mentioned other additives, for example, colorants, ultraviolet absorbers, light stabilizers, antistatic agents, flame retardants such as brominated polymers, antimony oxide, metal hydroxides, and phosphinates, flame retardant aids, crystal nucleating agents, plasticizers, lubricants, lubricants, dispersants, oxygen absorbers, hydrogen sulfide adsorbents, antioxidants, mold release agents, inorganic or organic fibrous fillers such as glass fibers, carbon fibers, and wholly aromatic polyamide fibers, powdered fillers such as wollastonite, silica, silica alumina, alumina, titanium dioxide, potassium titanate, magnesium hydroxide, molybdenum disulfide, carbon nanotubes, graphene, and polytetrafluoroethylene, and flaky fillers such as hydrotalcite, glass flakes, mica, clay, montmorillonite, and kaolin, etc. These may contain only one kind or two or more kinds.

[0145] The content of the other additives is not particularly limited unless the effects of the present invention are impaired, but is preferably 0.02 to 24% by mass, more preferably 0.05 to 20% by mass, further preferably 0.07 to 15% by mass, further preferably 0.07 to 10% by mass, and particularly preferably 0.07 to 5% by mass, relative to 100% by mass of the semi-aromatic polyamide (A).

[0146] The polyamide resin composition of the present embodiment preferably contains an antioxidant as an additive. As the antioxidant, for example, at least one selected from phenolic heat stabilizers, amine heat stabilizers, phosphorus heat stabilizers, and sulfur heat stabilizers is preferably used. By making the polyamide resin composition contain an antioxidant, it is easy to improve long-term heat resistance, and by using at least one selected from the above, it is possible to further achieve an improvement in long-term heat resistance.

[0147] The content of the antioxidant in the polyamide resin composition is preferably 0.1 to 2.0% by mass, more preferably 0.5 to 1.0% by mass.

[0148] <Polyamide resin compositions X1 to X4>

[0149] As a preferred embodiment of the polyamide resin composition of the present invention, the following polyamide resin compositions X1 to X4 are exemplified.

[0150] A polyamide resin composition X1 comprises a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C), and satisfies the following conditions [1a], [2a] and the above conditions [3] to [5].

[0151] [1a] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=63 / 37 to 84 / 16.

[0152] [2a] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.07 to 0.5% by mass based on the total mass of the semi-aromatic polyamide (A) and the polyolefin (B).

[0153] A polyamide resin composition X2 comprises a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C), and satisfies the following conditions [1b], [2b] and the above conditions [3] to [5].

[0154] [1b] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=68 / 32 to 82 / 18.

[0155] [2b] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.08 to 0.5% by mass based on the total mass of the semi-aromatic polyamide (A) and the polyolefin (B).

[0156] A polyamide resin composition X3 comprises a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C), and satisfies the following conditions [1c], [2c] and the above conditions [3] to [5].

[0157] [1c] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=73 / 27 to 85 / 15.

[0158] [2c] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.2 to 0.5% by mass based on the total mass of the semi-aromatic polyamide (A) and the polyolefin (B).

[0159] A polyamide resin composition X4 comprises a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C), and satisfies the following condition [1d], the above condition [2c] and the above conditions [3] to [5].

[0160] [1d] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=60 / 40 to 78 / 22.

[0161] [Method for producing polyamide resin composition]

[0162] The polyamide resin composition of the present embodiment can be produced, for example, by top-feeding the semi-aromatic polyamide (A), the polyolefin (B), and the aliphatic metal salt (C) into a twin-screw extruder and melt-kneading the mixture.

[0163] The method of melt kneading is not particularly limited, and a method that can uniformly mix the semi-aromatic polyamide (A), the polyolefin (B) and the aliphatic metal salt (C), and other additives used as needed, can be preferably adopted. As the melt kneading machine, a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc. are preferred, and a twin-screw extruder is more preferred from the viewpoint of good dispersibility of the polyolefin (B) and industrial productivity.

[0164] [Extrusion molded body and method for producing the same]

[0165] The extrusion molded product according to the embodiment of the present invention is an extrusion molded product of the above-mentioned polyamide resin composition.

[0166] The method for producing an extrusion molded article according to an embodiment of the present invention preferably includes the steps of heating and melting a polyamide resin composition and extruding the molten polyamide resin composition to obtain an extrusion molded article.

[0167] Compared with injection molding, extrusion molding has a low pressure and a slow flow rate applied to the material, so the material is easily retained in a molten state and easily deteriorates due to heat. In particular, in the molding of large pipes, the diameter of the mold becomes large, so the retention time of the material sometimes reaches tens of minutes. Therefore, in extrusion molding, a material with excellent retention stability is required. The polyamide resin composition of the present embodiment is due to its excellent retention stability, so it is not easy to deteriorate due to heat, and an extrusion molding with excellent quality can be obtained.

[0168] (Temperature and residence time during extrusion)

[0169] Generally, semi-aromatic polyamide has a high melting point, so the extrusion molding temperature tends to be high. The temperature during extrusion molding is preferably 10 to 60°C higher than the melting point, and when the residence time exceeds 5 minutes, it is preferably 10 to 40°C higher than the melting point.

[0170] Particularly when the residence time exceeds 5 minutes, the deterioration of the molded body becomes significant, so the polyamide resin composition of the present embodiment can be used appropriately. In addition, when the residence time exceeds 10 minutes, extremely high retention stability is required, and the polyamide resin composition of the present embodiment can also be used appropriately under such molding conditions.

[0171] In other words, a method for molding a polyamide resin composition according to one embodiment is a method for molding a polyamide resin composition as follows: using the above-mentioned polyamide resin composition satisfying conditions [1] to [5], molding is performed using an extruder under the condition that the temperature of the polyamide resin composition during extrusion molding is 10 to 40°C higher than the melting point of the polyamide resin composition, or under the condition that the residence time in the extruder exceeds 5 minutes and the temperature of the polyamide resin composition during extrusion molding is 10 to 40°C higher than the melting point of the polyamide resin composition, or under the condition that the residence time in the extruder exceeds 10 minutes and the temperature of the polyamide resin composition during extrusion molding is 10 to 40°C higher than the melting point of the polyamide resin composition.

[0172] (Resin pressure during extrusion molding)

[0173] The pressure applied to the material during extrusion molding (resin pressure during extrusion molding) is preferably as low as possible. If the pressure during extrusion molding is high, the speed of the screw needs to be reduced from the perspective of reducing the load of the extruder and safety. Therefore, in addition to the reduction in production speed, the material stays in the molding machine for a longer time, which is prone to thermal deterioration. It should be noted that by increasing the molding temperature, the pressure during molding can be reduced, but in this case, the problem of promoting material degradation due to heat occurs.

[0174] The polyamide resin composition of this embodiment satisfies the above conditions [1] to [5], especially condition [2], and can prevent the resin pressure from increasing during extrusion molding. Therefore, productivity is high, material degradation due to heat can be avoided, and the quality of the molded product can be improved.

[0175] (Application of extruded products)

[0176] As the above-mentioned extrusion molded body, for example, there can be mentioned molded bodies in the shape of films, sheets, tubes, monofilaments, multifilaments, pipes, round rods, wires, etc., and the molded body can be used for any parts such as automobile parts, industrial materials, industrial materials, electrical and electronic parts, mechanical parts, office equipment parts, household goods, etc. In particular, due to excellent chemical resistance, heat resistance, flexibility, and impact resistance, it can be suitably used as a chemical pipe, a composite pipe, a rodless oil production pipe, an onshore oil pipeline, an offshore oil pipeline, a geothermal flow pipe, an umbilical pipe, or a flexible pipe.

[0177] The polyamide resin composition of the present embodiment can be used to make a single-layer structure, and can also be used to make at least one layer in a multilayer structure. For example, in a tube having a single-layer structure or a multilayer structure, the polyamide resin composition of the present embodiment can be suitably used in at least one of the layers.

[0178] Example

[0179] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples at all.

[0180] The measurement of the physical properties of the materials used in Examples and Comparative Examples, and the measurement and evaluation of the physical properties of the compositions and films in Examples and Comparative Examples were performed according to the methods shown below.

[0181] (Measurement of various physical properties of semi-aromatic polyamide)

[0182] Intrinsic viscosity

[0183] For the semi-aromatic polyamide (sample) obtained in each Production Example, the intrinsic viscosity (dl / g) at a concentration of 0.2 g / dl and a temperature of 30° C. was determined from the following relational formula (S) using concentrated sulfuric acid as a solvent.

[0184] η inh = [ln (t1 / t0)] / c Formula (S)

[0185] In the above formula (S), η inh represents the intrinsic viscosity (dl / g), t0 represents the flow time (seconds) of the solvent (concentrated sulfuric acid), t1 represents the flow time (seconds) of the sample solution, and c represents the concentration (g / dl) of the sample in the sample solution (i.e., 0.2 g / dl).

[0186] Melting point

[0187] The melting point of the semi-aromatic polyamide obtained in each Production Example was measured using a differential scanning calorimeter “DSC7020” manufactured by Hitachi High-Tech Co., Ltd. in accordance with ISO 11357-3 (2011 2nd edition).

[0188] Specifically, first, in a nitrogen atmosphere, the sample (polyamide) was heated from 30°C to 300°C at a rate of 10°C / min, maintained at 300°C for 5 minutes to completely melt the sample, then cooled to 50°C at a rate of 10°C / min, and maintained at 50°C for 5 minutes. The peak temperature of the melting peak that appeared when the temperature was again raised to 300°C at a rate of 10°C / min was taken as the melting point (°C). If there were multiple melting peaks, the peak temperature of the melting peak on the highest temperature side was taken as the melting point (°C).

[0189] Terminal amino content

[0190] 1 g of the semi-aromatic polyamide obtained in each manufacturing example was dissolved in 35 mL of phenol, and 2 mL of methanol was mixed therein to prepare a sample solution. Using thymol blue as an indicator, titration with a 0.01 N hydrochloric acid aqueous solution was performed to measure the terminal amino group content ([NH2], unit: μeq / g) of the semi-aromatic polyamide.

[0191] Terminal carboxyl content

[0192] 0.5 g of the semi-aromatic polyamide obtained in each manufacturing example was dissolved in 40 mL of o-cresol to prepare a sample solution. The sample solution was titrated using a 0.01 N ethanolic potassium hydroxide solution using a potentiometric titration apparatus manufactured by Kyoto Electronics Co., Ltd., and the inflection point of the potential was detected to determine the terminal carboxyl group content ([COOH], unit: μeq / g) of the semi-aromatic polyamide.

[0193] (Evaluation of polyamide resin composition and extruded molded product thereof)

[0194] ·Manufacturing stability of polyamide resin compositions

[0195] In Examples and Comparative Examples, processing stability when producing a polyamide resin composition using a twin-screw extruder was evaluated based on the following two-stage criteria.

[0196] A: There is no bend at the vacuum exhaust port and no breakage of the strands, and stable manufacturing is possible.

[0197] B: The stability of the strands is reduced, and there is a tendency for volatilized materials to accumulate at the vacuum exhaust port, which raises concerns about manufacturing stability.

[0198] ·Appearance of extruded products at high temperature

[0199] Using a tube forming device connected to a straight die (die inner diameter: φ21.0 mm, mandrel outer diameter: φ14.9 mm) on a single screw extruder (screw diameter: φ50 mm, L / D=28) manufactured by AGI Co., Ltd., the polyamide resin compositions obtained in the Examples and Comparative Examples were discharged for 30 minutes under the conditions of a barrel temperature of 300°C, a die temperature of 300°C, and a screw speed of 5 rpm / 30 rpm. The molded bodies were then discharged, and the appearance of the molded bodies was visually confirmed and evaluated according to the following criteria. It should be noted that the residence time inside the molding machine at screw speeds of 5 rpm and 30 rpm was 15 minutes and 2.5 minutes, respectively.

[0200] A: The surface of the molded body is smooth and glossy.

[0201] B: The surface of the molded article has irregularities.

[0202] Resin pressure during extrusion

[0203] The polyamide resin compositions obtained in the examples and comparative examples were discharged using the above-mentioned tube forming apparatus at a barrel temperature of 280°C, a die temperature of 280°C, and a screw speed of 30 rpm, and the resin pressure was measured using a pressure gauge connected to the front end of the barrel of the single-screw extruder.

[0204] ·Surface smoothness of extruded products (tubes)

[0205] The polyamide resin compositions obtained in Examples and Comparative Examples were discharged using the above-mentioned tube forming apparatus under the conditions of a barrel temperature of 280°C, a mold temperature of 280°C, and a screw speed of 30 rpm. Next, the dimensions were controlled and cooled in a vacuum dimension adjustment tank, and the centerline average roughness (Ra) in the flow direction of the outer surface of a tube with an outer diameter of 8.0 mm and an inner diameter of 6.0 mm formed at a pulling speed of 10 m / min was measured using a contact surface roughness meter (SP-85DS2) manufactured by Kosaka Laboratory Co., Ltd.

[0206] ·Tensile properties of extruded products (tubes)

[0207] The produced tube was used to measure the tensile elongation at break (%) at 23° C. using Autograph (manufactured by Instron) in accordance with SAE J2260. A larger value of the tensile elongation at break indicates better elongation properties. The measurement conditions are as follows.

[0208] Stretching speed: 50mm / min

[0209] Test length (between fixtures): 150mm

[0210] Clamping length: 50mm at each end

[0211] ·Production of dumbbell test pieces

[0212] Using an injection molding machine manufactured by Sumitomo Heavy Industries, Ltd. (mold clamping force: 100 tons, screw diameter: φ32 mm), the polyamide resin composition obtained in the Examples and Comparative Examples was molded using a T-channel mold under the conditions of a barrel temperature set to 20 to 30°C higher than the melting point of the semi-aromatic polyamide and a mold temperature of 140°C to prepare a multi-purpose test piece A1 type (a dumbbell-shaped test piece described in JIS K7139: 2009; 4 mm thick, 170 mm in total length, 80 mm in parallel portion length, and 10 mm in parallel portion width). Then, a rectangular parallelepiped test piece (size: length×width×thickness=80 mm×10 mm×4 mm) was cut out from the multi-purpose test piece as a test piece for evaluation of the tensile test and the impact resistance test.

[0213] Tensile test

[0214] The multipurpose test piece A1 (4 mm thick) prepared by the above method was used to measure the tensile strength (maximum point) (MPa) at 23° C. and a tensile speed of 50 mm / min using Autograph (manufactured by Instron) in accordance with ISO527-1 (2012 2nd edition).

[0215] Flexural modulus

[0216] The multipurpose test piece A1 type (4 mm thick) prepared by the above method was used to measure the flexural modulus (GPa) at 23° C. using Autograph (manufactured by Instron) in accordance with ISO 178. The measurement was performed at a bending speed of 2 mm / min.

[0217] From the viewpoint of flexibility of the extruded product, the flexural modulus is preferably 1.7 GPa or less.

[0218] Impact resistance

[0219] Test pieces (4 mm thick, 80 mm long, 10 mm wide, notched) were cut from the multipurpose test piece A1 type (4 mm thick) prepared by the above method. The notched Charpy impact values ​​at 23°C and -40°C were measured using an impact tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ISO179-1 (2010 2nd edition) to evaluate the impact resistance (kJ / m 2 ).

[0220] Chemical resistance

[0221] The test piece for tensile test prepared by the above method was immersed in automobile engine coolant (Toyota genuine super long-life coolant / water = 50 / 50 volume ratio) in a pressure-resistant container and left to stand for 1,000 hours in a constant temperature bath ("DE-303" manufactured by Mita Sangyo Co., Ltd.) set at 130°C. After 1,000 hours, the test piece was taken out and subjected to a tensile test at 23°C by the same method as above to measure the tensile strength after chemical reagent immersion.

[0222] The tensile strength retention rate was calculated by the following formula (T) to evaluate the chemical resistance.

[0223] Tensile strength retention rate (%)

[0224] = (tensile strength after 1,000 hours / initial tensile strength) × 100 Formula (T)

[0225] [Manufacturing example]

[0226] Production Example 1 [Production of semi-aromatic polyamide (A): PA-1]

[0227] 9871.2 g (59.42 mol) of terephthalic acid, 9639.3 g (60.90 mol) of a mixture of 1,9-nonanediamine and 2-methyl-1,8-octanediamine [50 / 50 (molar ratio)], 142.9 g (1.17 mol) of benzoic acid, 9.8 g (0.05 mass % relative to the total mass of the raw materials) of sodium hypophosphite monohydrate and 5 liters of distilled water were added to an autoclave with an internal volume of 40 liters and purged with nitrogen. While stirring, the temperature inside the autoclave was raised to 220°C over 2 hours. At this time, the pressure inside the autoclave was raised to 2 MPa. After continuing the reaction for 2 hours in this state, the temperature was raised to 230°C, and then the temperature was maintained at 230°C for 2 hours, and the reaction was allowed to proceed while slowly discharging water vapor and maintaining the pressure at 2 MPa. Next, the pressure was reduced to 1 MPa over 30 minutes, and the reaction was further allowed to proceed for 1 hour to obtain the characteristic viscosity η inh The prepolymer is 0.2 dL / g.

[0228] The obtained product was crushed to a particle size of less than 2 mm using a Hosokawa Micron flake crusher, dried at 100°C under reduced pressure for 12 hours, and then solid-phase polymerized at 230°C and 13 Pa (0.1 mmHg) for 10 hours to obtain a white semi-aromatic polyamide (A) (semi-aromatic polyamide PA-1). The semi-aromatic polyamide PA-1 as the semi-aromatic polyamide (A) is composed of terephthalic acid units, 1,9-nonanediamine units, and 2-methyl-1,8-octanediamine units (1,9-nonanediamine units / 2-methyl-1,8-octanediamine units = 50 / 50 (molar ratio)), has a melting point of 265°C, and an intrinsic viscosity η inh The content of terminal amino groups ([NH2]) is 1.28 dL / g, the content of terminal amino groups ([NH2]) is 51.5 μeq / g, and the content of terminal carboxyl groups ([COOH]) is 23.4 μeq / g. That is, the value of [NH2] / [COOH] of the semi-aromatic polyamide PA-1 is 2.2, which satisfies the above condition [3].

[0229] Production Example 2 [Production of semi-aromatic polyamide: PA-2]

[0230] 9871.2 g (59.42 mol) of terephthalic acid, 9544.3 g (60.30 mol) of a mixture of 1,9-nonanediamine and 2-methyl-1,8-octanediamine [50 / 50 (molar ratio)], 142.9 g (1.17 mol) of benzoic acid, 9.8 g (0.05% by mass relative to the total mass of the raw materials) of sodium hypophosphite monohydrate and 5 liters of distilled water were added to an autoclave with an internal volume of 40 liters and purged with nitrogen. Then, polymerization was carried out in the same manner as in Preparation Example 1 to obtain a semi-aromatic polyamide PA-2 other than the semi-aromatic polyamide (A). The melting point of the semi-aromatic polyamide PA-2 is 265°C, and the characteristic viscosity η inh The [NH2] / [COOH] value of the semi-aromatic polyamide PA-2 is 0.28, which does not satisfy the above condition [3].

[0231] [Examples and Comparative Examples]

[0232] The polyamide resin compositions of the examples and comparative examples were prepared according to the formulations shown in Table 1 and Table 2.

[0233] Specifically, the semi-aromatic polyamide, fatty acid metal salt (C), copper stabilizer, antioxidant, lubricant, release agent, and colorant shown in Table 1 and Table 2 were pre-mixed in the mass ratio shown in Table 1 and Table 2, and put into the upstream feed port of the twin-screw extruder ("TEM-26SS" manufactured by Toshiba Machine Co., Ltd.) together with the type and mass ratio of polyolefin shown in Table 1 and Table 2. Melt kneading was carried out under the conditions of barrel temperature of 300-320°C (melt kneading temperature of 310-340°C, melt kneading temperature represents resin temperature), rotation speed of 150rpm, and discharge of 10kg / hr, thereby kneading and extruding, cooling and cutting, thereby preparing a pelletized polyamide resin composition. The above pellets were used to make test pieces for various physical property evaluations, and various evaluations were carried out using the above methods. The results are shown in Tables 1 and 2.

[0234] The details of the components shown in Tables 1 and 2 are as follows.

[0235] <Semi-aromatic polyamide (A): PA-1>

[0236] Semi-aromatic polyamide PA-1 obtained in Production Example 1

[0237] <Semi-aromatic polyamide other than semi-aromatic polyamide (A): PA-2>

[0238] Semi-aromatic polyamide PA-2 obtained in Production Example 2

[0239] <Polyolefin (B)>

[0240] · Mitsui Chemicals, Inc., TAFMER MH7010: Maleic anhydride-modified ethylene-butene copolymer [anhydride group content: 50 μmol / g]

[0241] · Mitsui Chemicals, Inc., TAFMER MH5010: Maleic anhydride-modified ethylene-butene copolymer [anhydride group content: 50 μmol / g]

[0242] · Mitsui Chemicals, Inc., TAFMER MP0620: Maleic anhydride-modified ethylene-propylene copolymer [anhydride group content: 100 μmol / g]

[0243] · Arkema, Lotader 4700: Copolymer of ethylene, ethyl acrylate and maleic anhydride [Et / EA / MAH = 68.7 / 30 / 1.3 (mass ratio)]

[0244] <Polyolefins other than polyolefin (B)>

[0245] · Arkema, Lotader AX8900: Copolymer of ethylene, methyl acrylate and glycidyl methacrylate [Et / MA / GMA = 68 / 24 / 8 (mass ratio)]

[0246] <Aliphatic metal salt (C)>

[0247] · CALCIUM STEARATE S (CaSt) manufactured by NOF Corporation

[0248] <Copper stabilizer>

[0249] ·KG HS-01P manufactured by PolyAd Services (Copper atomic ratio in KG HS-01P: 3.4 mass %)

[0250] <Antioxidants>

[0251] Sumitomo Chemical Co., Ltd., SUMILIZER GA-80 (phenolic heat stabilizer): 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane

[0252] · Addivant, Naugard 445 (amine-based heat stabilizer): 4,4'-bis(α,α-dimethylbenzyl)diphenylamine

[0253] <Lubricant>

[0254] ·Made by Kyoeisha Chemical Co., Ltd., amide wax light amide WH-255

[0255] <Mold release agent>

[0256] ·Made by Clariant Japan Co., Ltd., LicowaxOP

[0257] <Coloring agent>

[0258] ·Mitsubishi Chemical Corporation, Carbon Black #980B

[0259] [Table 1]

[0260]

[0261] [Table 2]

[0262]

[0263] The results in Table 1 show that the polyamide resin compositions of Examples 1 to 6 satisfying all of the above conditions [1] to [5] have good production stability and excellent retention stability.

[0264] In addition, it can be seen from Tables 1 and 2 that the pressure increase during molding is suppressed, and the obtained tube has excellent surface properties, and is excellent in flexibility, chemical resistance, and impact resistance in a wide temperature range. In addition, it can be seen that the tube as an extruded molded product of the polyamide resin composition satisfying the above conditions [1] to [5] has excellent surface properties, and is excellent in flexibility, chemical resistance, and impact resistance in a wide temperature range, and has high elongation characteristics.

[0265] On the other hand, as can be seen from Tables 1 and 2, the polyamide resin composition of Comparative Example 5, which does not contain the fatty acid metal salt (C) and does not satisfy the condition [2], has good production stability and retention stability, but the resin pressure during extrusion molding is significantly increased compared to the polyamide resin compositions of Examples 1 to 6.

[0266] In addition, as can be seen from Tables 1 and 2, the polyamide resin composition of Comparative Example 8, which has a high content of the fatty acid metal salt (C) and does not satisfy condition [2], has good retention stability, but has reduced production stability, and the elongation characteristics of the extruded product and the impact resistance in the low temperature region are also reduced.

[0267] In addition, as can be seen from Tables 1 and 2, the polyamide resin composition of Comparative Example 3, which has a large content of copper-based stabilizer and does not satisfy condition [5], has reduced retention stability, and compared with the polyamide resin composition of Example 1 having the same mass ratio of components (A) and (B), the resin pressure during extrusion molding becomes larger, and the elongation characteristics of the extruded molded product are also reduced.

[0268] In addition, as can be seen from Tables 1 and 2, the polyamide resin composition of Comparative Example 4, which has a large content of copper-based stabilizer and does not satisfy condition [5], has reduced retention stability, and the elongation characteristics of the extruded molded product and the impact resistance in the low temperature region are significantly reduced compared to the polyamide resin composition of Example 3, which has the same mass ratio of components (A) and (B).

[0269] In addition, as shown in Tables 1 and 2, the polyamide resin compositions of Comparative Examples 6 and 7 using polyolefins that do not satisfy the above condition [4] have reduced retention stability, significantly increased resin pressure during extrusion molding, and reduced elongation properties of the extruded molded product.

[0270] In addition, as can be seen from Table 1, the polyamide resin composition of Comparative Example 2 using the semi-aromatic polyamide PA-2 that does not satisfy the above condition [3] has a reduced retention stability, and compared with the polyamide resin composition of Example 1 having the same mass ratio of components (A) and (B), the resin pressure during extrusion molding increases, and the chemical resistance and elongation characteristics of the extruded product and the impact resistance in the low temperature region are reduced.

[0271] In addition, according to Table 1, the polyamide resin composition of Comparative Example 1 using the semi-aromatic polyamide PA-2 that does not satisfy the above condition [3] has lower chemical resistance and elongation characteristics and impact resistance in the low temperature region of the extruded product than the polyamide resin composition of Example 1, and the resin pressure during extrusion molding also increases, even if the mass ratio of component (A) to component (B) is made larger than that of Example 1.

[0272] In addition, it is clear from Table 2, the comparison between Comparative Examples 6 and 7, and the comparison between Comparative Examples 3 and 5 and Comparative Example 7 that, in the case of a polyamide resin composition using a polyolefin having an unsaturated epoxide-containing functional group, even if a fatty acid metal salt (C) is added, the effect of reducing the resin pressure during extrusion molding cannot be obtained. In other words, it is understood that the effect of reducing the resin pressure during extrusion molding cannot be obtained because the above-mentioned condition [4] is not satisfied.

Claims

1. A polyamide resin composition comprising a semi-aromatic polyamide (A), a polyolefin (B) and a fatty acid metal salt (C), and satisfying the following conditions [1] to [5], [1] The ratio of the mass MA of the semi-aromatic polyamide (A) to the mass MB of the polyolefin (B) in the polyamide resin composition is MA / MB=60 / 40 to 85 / 15, [2] The content of the fatty acid metal salt (C) in the polyamide resin composition is 0.05% by mass to 0.5% by mass based on the total mass of the semi-aromatic polyamide (A) and the polyolefin (B). [3] The terminal amino group concentration [NH2] of the semi-aromatic polyamide (A) is 45 μeq / g to 80 μeq / g and the ratio of the terminal amino group concentration to the terminal carboxyl group concentration [COOH] of the semi-aromatic polyamide (A) satisfies the following formula (1), wherein the units of the terminal amino group concentration and the terminal carboxyl group concentration are μeq / g, 2<[NH2] / [COOH]<5 ···Formula (1) [4] The polyolefin (B) does not contain a functional group formed by an unsaturated epoxide, or the content ratio of the functional group formed by an unsaturated epoxide in the polyolefin (B) is 200 μmol / g or less, [5] The polyamide resin composition does not contain a copper-based stabilizer, or the copper atomic ratio derived from the copper-based stabilizer in the polyamide resin composition is 200 mass ppm or less.

2. The polyamide resin composition according to claim 1, wherein The semi-aromatic polyamide (A) contains 50 mol % or more of at least one selected from terephthalic acid units and naphthalene dicarboxylic acid units based on all dicarboxylic acid units.

3. The polyamide resin composition according to claim 1 or 2, wherein The semi-aromatic polyamide (A) contains 60 mol % or more of an aliphatic diamine unit having 7 to 13 carbon atoms or a meta-xylylenediamine unit based on all diamine units.

4. The polyamide resin composition according to claim 3, wherein The aliphatic diamine unit having 7 to 13 carbon atoms is a unit derived from at least one aliphatic diamine selected from 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine and 1,10-decanediamine.

5. The polyamide resin composition according to claim 3 or 4, wherein The aliphatic diamine unit having 7 to 13 carbon atoms is a unit derived from at least one aliphatic diamine selected from 1,9-nonanediamine and 2-methyl-1,8-octanediamine.

6. The polyamide resin composition according to any one of claims 1 to 5, wherein The polyolefin (B) is a modified polyolefin modified with at least one selected from the group consisting of α,β-unsaturated carboxylic acids and derivatives thereof.

7. The polyamide resin composition according to any one of claims 1 to 6, wherein The fatty acid metal salt (C) is a metal salt of a fatty acid having 10 to 28 carbon atoms.

8. The polyamide resin composition according to any one of claims 1 to 7, wherein The fatty acid metal salt (C) is selected from calcium stearate, magnesium stearate and zinc stearate. 9 . The polyamide resin composition according to claim 1 , comprising an antioxidant. 10 . An extrusion molded product, which is an extrusion molded product of the polyamide resin composition according to claim 1 . 11 . The extruded article according to claim 10 , which is a chemical pipe, a composite pipe, a rodless production pipe, an onshore oil pipeline, an offshore oil pipeline, a geothermal flow pipe, an umbilical pipe, or a flexible pipe.

12. A method for producing an extruded body, wherein: The polyamide resin composition according to any one of claims 1 to 9 is heated and melted, and the molten polyamide resin composition is extruded to obtain an extruded molded product.

Citation Information

Patent Citations

  • Semi-aromatic polyamide resin

    JP2013040346A

  • Multilayer composite material having layer composed of partial aromatic polyamide

    JP2016172445A